Biology for engineers - Johnson, Arthur T. 1941- (CRC Press, Taylor & Francis Group, 2019)
Biology is a critical application area for engineering analysis and design, and students in engineering programs as well as ecologists and environmentalists must be well-versed in the fundamentals of biology as they relate to their field. Biology for Engineers, Second Edition is an introductory text that minimizes unnecessary memorization of connections and classifications and instead emphasizes concepts, technology, and the utilization of living things. Whether students are headed toward a bio-related engineering degree or one of the more traditional majors, biology is so important that all engineering students should know how living things work and act. Emphasizing the ever-present interactions between a biological unit and its physical, chemical, and biological environments, the book provides ample instruction on the basics of physics, chemistry, mathematics, and engineering through a systems approach. It brings together all the concepts one needs to understand the role of biology in modern technology. Classroom-tested at the University of Maryland, this comprehensive text introduces concepts and terminology needed to understand more advanced biology literature. Filled with practical detailed examples, the book presents: Presents scientific principles relevant to biology that all engineers, ecologists and environmentalists must know A discussion of biological responses from the perspective of a broad range of fields such as psychology, human factors, genetics, plant and animal physiology, imaging, control systems, actuary, and medicine Includes end of chapter questions to test comprehension Provides updated material to reflect the latest research developments such as CRISPR. Introduces over 150 interesting application examples, incorporating a number of different engineering disciplines. Ties biological systems properties and behaviors to foundational sciences such as engineering sciences, chemistry, etc.